Tracheobronchial Tear in Emergency Care: Rapid Recognition, Airway Stabilization, and Definitive Management Strategies - Alenezi, Guoom Gazam Mohamad; Mohammed Ali Ali Nushayli,; Mohammed Ahmed Yahya Ghazwani,; Mohammed Ahmad Rajhi,; Yahya Ali Jaber Nushayli,; Majed Mohammed Ali Sowedi,; Mohammed Ali Mohammed Mobarki,; Yahya Alawi Yahya Dibaji,; Yahay Mohammed Ali Awaji,; Faisal Fahad Ali Aljahlan,; Ibrahim Mohammed Agili,; Abdo Hassan Mohammed Khobrani,; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Tracheobronchial tear is a rare but life-threatening airway injury resulting from blunt or penetrating trauma or iatrogenic interventions. Its diagnostic challenge and high mortality underscore the need for rapid recognition and effective management. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> To review the etiology, epidemiology, pathophysiology, diagnostic strategies, and management principles of tracheobronchial tears in emergency care settings. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive literature-based analysis was conducted, synthesizing evidence from trauma registries, postmortem studies, and clinical series. Mechanisms of injury, diagnostic modalities, and treatment approaches were examined to identify best practices for emergency and perioperative care. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Tracheobronchial injuries occur predominantly near the carina and main bronchi, with blunt trauma associated with higher mortality than penetrating injuries. Up to 70% of cases are initially missed, often presenting with nonspecific signs such as persistent pneumothorax and subcutaneous emphysema. Fiberoptic bronchoscopy remains the gold standard for diagnosis and airway stabilization. Definitive management typically involves surgical repair, although conservative and endoscopic strategies are viable for select iatrogenic injuries. Prognosis improves significantly with early recognition and multidisciplinary intervention. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Early suspicion, bronchoscopy-guided airway control, and mechanism-sensitive management are critical to reducing morbidity and mortality. Structured trauma protocols and preventive measures for iatrogenic injury can further enhance outcomes.